Human platelet lysate promotes proliferation but fails to maintain chondrogenic markers of chondrocytes - Prana Hardinata Budi Harto,; Muhammad Hanif Mahmud,; Aisya Hanim Othman,; Nurulain Hanani Ngadenin,; Nur Saihah Mohd Azahar,; Muhammad Najib Fathi Hassan,; Nor Hamdan Mohd Yahaya,; Rizal Abdul Rani,; Leong, Chooi Fun; Ng, Min Hwei; Law, Jia Xian (Penerbit Universiti Kebangsaan Malaysia, 2019)
Traditionally, foetal bovine serum (FBS) is used as a serum supplement for stem cell expansion in vitro. However, it is associated with xenoimmunisation and the transmission of animal pathogens, which may cause harm to stem cell recipients. As a safer alternative, human platelet lysate (HPL) has been introduced for propagating stem cells. Chondrocytes are expanded in vitro for cartilage repair via autologous chondrocyte implantation (ACI). In this study, we compare the efficacy of HPL prepared from expired platelet concentrates with that of FBS for promoting the proliferation and maintenance of the chondrogenic markers of primary human chondrocytes expanded in vitro. Chondrocytes were cultured in F12:Dulbecco’s modified Eagle’s medium (DMEM) supplemented with 5% HPL, 10% HPL and 10% FBS. The cell morphology, viability and growth rate were examined from passage 1 (P1) to P3. RNA was isolated from P3 cells for quantitative polymerase chain reaction (qPCR) to determine the gene expression level of the chondrogenic, dedifferentiation and hypertrophic markers. HPL promoted chondrocyte proliferation without compromising cell viability. In addition, the chondrocytes cultured with HPL were smaller. However, HPL failed to maintain the chondrogenic markers, except SOX 9 (SRY-box transcription factor 9), which was upregulated, but not significantly. Nonetheless, HPL also suppressed the expression of type X collagen (Col X), a chondrocyte hypertrophic marker. In summary, we demonstrate the benefits of HPL supplementation in human chondrocyte culture, where it enhances cell proliferation and suppresses chondrocyte hypertrophy. In the future, HPL can be used for the large-scale expansion of chondrocytes for ACI.